2018
DOI: 10.1002/cbic.201700470
|View full text |Cite
|
Sign up to set email alerts
|

Exploring PTDH–P450BM3 Variants for the Synthesis of Drug Metabolites

Abstract: The conversion of a series of pharmaceutical compounds was examined with three variants of cytochrome P450BM3 fused to phosphite dehydrogenase (PTDH) to enable cofactor recycling. Conditions for enzyme production were optimized, and the purified PTDH-P450BM3 variants were tested against 32 commercial drugs by using rapid UPLC-MS analysis. The sets of mutations (R47L/F87V/L188Q and R47L/F87V/L188Q/E267V/G415S) improved conversion for all compounds, and a variety of products were detected. Product analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…Even though the fusion is rather large (155 kDa), expression is not compromised. The authors demonstrated the utility of PTDH–P450 by converting several pharmaceutical compounds to hydroxylated drug metabolites . A similar study was performed with a heterotrimeric P450 from Pseudonomas putida , in which it was fused to PTDH for self‐sufficient hydroxylations …”
Section: Enzyme Fusions In Biocatalysismentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the fusion is rather large (155 kDa), expression is not compromised. The authors demonstrated the utility of PTDH–P450 by converting several pharmaceutical compounds to hydroxylated drug metabolites . A similar study was performed with a heterotrimeric P450 from Pseudonomas putida , in which it was fused to PTDH for self‐sufficient hydroxylations …”
Section: Enzyme Fusions In Biocatalysismentioning
confidence: 99%
“…The authors demonstrated the utility of PTDH-P450 by converting several pharmaceutical compounds to hydroxylated drug metabolites. [12,33] As imilar study was performed with ah eterotrimeric P450 from Pseudonomas putida, in whichi tw as fused to PTDH for self-sufficienth ydroxylations. [34] Enzyme fusion can be ag reat way to generate ac ofactor or cosubstrate forap articulare nzyme reaction.…”
Section: Heme-containing Enzymes:cytochrome P450 and Peroxidase Fusionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] We have adopted as imilar approach based on CYP102A1 variants found to have increased activity for unnatural substrate oxidation as aresult of the interaction between the heme iron and the axial water being weakened by anumber of mechanisms. [13] We report here the oxidation of THQs and quinolines by CYP102A1 variants with the aim to functionalize these building-block molecules selectively at as many positions as possible and thus provide synthetic handles to compounds with biological activity.F urther to C À Hb ond oxidation, we found that CYP102A1 displayed other oxidase activities, including desaturation, [14] aromatization, [15] and CÀCb ond formation reactions. [13] We report here the oxidation of THQs and quinolines by CYP102A1 variants with the aim to functionalize these building-block molecules selectively at as many positions as possible and thus provide synthetic handles to compounds with biological activity.F urther to C À Hb ond oxidation, we found that CYP102A1 displayed other oxidase activities, including desaturation, [14] aromatization, [15] and CÀCb ond formation reactions.…”
mentioning
confidence: 85%